Answer:
(3a³-5b³)+ (-2)a³ +6b³=(a³+b³)
Explanation:
First, lets remove the brackets. There is no "-" before the brackets, so we can just remove them at all.
3a³-5b³+ ...a³ +...b³=a³+b³
Now we can joint similar monoms (with variable a) ( and with variable b) in the left side of equation
3a³+...a³ -5b³ +...b³=a³+b³
Now we can notice that 3a³+...a³=a³ (1) and
-5b³ +...b³=b³ (2)
Lets find deduct 3a³ from both sides of (1)
...a³= a³-3a³
...a³= -2a³ So instead ... we have to type -2 (-2 is negative sowe type -2 in brackets).
Similarly lets add 5b³ to both sides of (2)
-5b³ +...b³=b³
-5b³ +5b³ +...b³=b³+5b³
...b³=6b³ So instead ... we have to type 6.